The Right Amount of Panic : How Women Trade Freedom for Safety - Vera-Gray, F. (Book collections on Project MUSE., 2018)
Have you ever thought about how much energy goes into avoiding sexual violence? The work that goes into feeling safe goes largely unnoticed by the women doing it and by the wider world, and yet women and girls are the first to be blamed the inevitable times when it fails. We need to change the story on rape prevention and 'well-meaning' safety advice, because this makes it harder for women and girls to speak out, and hides the amount of work they are already doing trying to decipher 'the right amount of panic'. With real-life accounts of women's experiences, and based on the author's original research on the impact of sexual harassment in public, this book challenges victim-blaming and highlights the need to show women as capable, powerful and skilful in their everyday resistance to harassment and sexual violence.